Natural severe fever with thrombocytopenia syndrome virus infection in domestic cats in Japan - Matsuu, Aya; Momoi, Yasuyuki; Nishiguchi, Akihiro; Noguchi, Keita; Yabuki, Mihoko; Hamakubo, Emu; Take, Maho; Maeda, Ken (Veterinary microbiology, 2019)
•SFTSV infection in cats was characterized by an acute onset and high mortality.•Cats infected with SFTSV showed fever, icterus, thrombocytopenia, and leukopenia frequently.•Outdoor cats were commonly at risk of SFTSV infection in the endemic area.•The almost cat SFTSV was genetically close to human SFTSV.•SFTS in cats is a public health issue, affecting pet owners and animal hospitals. Severe fever with thrombocytopenia syndrome (SFTS) is a recently discovered emerging infectious disease. A zoonotic disease with a high fatality rate in human beings, clinical information on SFTS virus (SFTSV) infection in animals is important. Since 2017, we have diagnosed 24 client-owned cats living in western Japan with SFTS, by genetic and serological testing. In this study, we characterized the clinical features of SFTS in cats and their associated risk factors, by evaluating the clinical parameters retrospectively. A phylogenetic analysis on SFTSV was also conducted. There were no obvious tendencies in age or sex, outdoor cats were commonly at risk of SFTSV infection. All infected cats showed acute onset of clinical signs including anorexia and lethargy, while 68.2% of the cats showed fever and 41.7% showed vomiting. The case fatality rate was 62.5%. Thrombocytopenia, leukopenia, and elevated serum total bilirubin, serum amyloid A, and creatinine phosphokinase concentration were the characteristic findings in the first clinical blood examination. Phylogenic analysis revealed that regional clustered viruses infect both humans and cats. For pet owners and animal hospitals, SFTS in small animals could be an important public health issue.